2007
DOI: 10.1016/j.pbb.2007.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Rotation and immediate-early gene expression in rats treated with the atypical D1 dopamine agonist SKF 83822

Abstract: Classical agonists of the dopamine D1 receptor activate both adenylyl cyclase and phospholipase C (PLC) signaling pathways. As a result, the extent to which these two pathways are essentially involved in various effects produced by D1 receptor agonists is currently uncertain. In the present report we examined the effects of SKF 83822, a dopamine D1 agonist which has been reported to activate adenylyl cyclase, but not PLC, on behavior and immediate early gene (IEG) expression in rats with unilateral 6-hydroxydo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…In the present study, ELF-MF-induced long-lasting FRA expression in the striatal complex was attenuated by SCH23390, a dopaminergic D1 antagonist, but not by sulpiride, a dopaminergic D2 antagonist, suggesting that ELF-MF induces long-lasting FRA-IR via stimulation of dopaminergic D1 receptor. These results are in line with previous findings showing that direct stimulation of D1 receptor with specific agonist ( Wirtshafter, 2007 ) or indirect stimulation of D1 receptor with psychostimulants ( Young et al, 1991 ; Bronstein et al, 1996 ; Zhang et al, 2002 ) augments FRA expression in the striatal complex. Especially, it has been suggested that dopaminergic D1 receptor-mediated adenylate cyclase signaling pathway, but not phospholipace C pathway, is necessary for inducing FRA in the striatum ( Wirtshafter, 2007 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, ELF-MF-induced long-lasting FRA expression in the striatal complex was attenuated by SCH23390, a dopaminergic D1 antagonist, but not by sulpiride, a dopaminergic D2 antagonist, suggesting that ELF-MF induces long-lasting FRA-IR via stimulation of dopaminergic D1 receptor. These results are in line with previous findings showing that direct stimulation of D1 receptor with specific agonist ( Wirtshafter, 2007 ) or indirect stimulation of D1 receptor with psychostimulants ( Young et al, 1991 ; Bronstein et al, 1996 ; Zhang et al, 2002 ) augments FRA expression in the striatal complex. Especially, it has been suggested that dopaminergic D1 receptor-mediated adenylate cyclase signaling pathway, but not phospholipace C pathway, is necessary for inducing FRA in the striatum ( Wirtshafter, 2007 ).…”
Section: Discussionsupporting
confidence: 93%
“…The smaller number of egr1 + neurons after directed singing could be a consequence of a dominant function of D2 receptors in D1A + /D2 + cells with high dopamine levels. However, it has been found that synergistic activation of D1-like and D2-like receptors in the same neurons can lead to even greater increases in egr1 expression than the activation of D1-like receptors alone ( Keefe and Gerfen, 1995 ; Wirtshafter, 2007 ). If this were to occur in intact brain, then an alternative mechanisms could be responsible for the social context differences, such as the affinity state of D2 receptors and the amount of dopamine release ( Richfield et al, 1989 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests dopamine (DA) D1 receptor stimulation is necessary for the expression of Arc (Fosnaugh et al, 1995;Fumagalli et al, 2006;Granado et al, 2007;Wirtshafter, 2007;Yamagata et al, 2000) and DA D1 receptors play a critical role in cocaineseeking behavior elicited by cocaine cues (Alleweireldt et al, 2002(Alleweireldt et al, , 2003Khroyan et al, 2000). Accordingly, DA D1 receptors within the prefrontal cortex may have contributed to the conditioned increases in Arc mRNA levels in animals engaged in cue-induced reinstatement of extinguished cocaine-seeking behavior in the present study.…”
Section: Discussionmentioning
confidence: 99%